Structure and assembly of a hexanuclear AuNi bimetallic nanocluster. Issue 1 (7th December 2022) - Tao, Cheng-Bo; Fan, Ji-Qiang; Fei, Wenwen; Zhao, Yan; Li, Man-Bo
Abstract : An Au4 Ni2 nanocluster containing a square-planar [PPh2 –Au–S–Au]2 ring and two nickel-pincer arms was found to be assembled by noncovalent interactions. The assembly-dependent properties that are distinct from the octahedral M6 clusters were shown. Abstract : An Au4 Ni2 nanocluster containing a square-planar [–PPh2 –Au–S–Au–]2 ring and two nickel-pincer arms is reported here. Abundant intra- and inter-cluster noncovalent interactions promote the assembly of the nanocluster into a porous framework material. The assembly-dependent unique solubility and photoluminescence were also investigated.